Evaluation of the antioxidant and antimicrobial properties of in vitro cultured Drosera intermedia extracts - Grevenstuk, Tomás (2013)
Evaluation of the antioxidant activity of the methanol, water and n-hexane extracts of Drosera intermedia, determined by the Folin-Ciocalteau (F-C), trolox equivalent antioxidant capacity (TEAC) and oxygen radical antioxidant capacity (ORAC) assays showed that the methanol extract had the highest antioxidant activity (F-C: 378.6 ± 31.5 μmolGAE/mgextract; TEAC: 332.2 ± 29.1 μmolTE/mgextract; ORAC: 64.7 ± 7.8 μmolTE/mgextract). Antimicrobial activity was tested against seven bacterial and eight yeast strains using the agar diffusion assay, followed by the determination of minimum inhibitory concentrations (MIC). All tested D. intermedia extracts demonstrated strong antimicrobial properties with a broad spectrum of activity. However, the n-hexane extract exhibited much greater activity than water and methanol extracts. The most susceptible microorganisms to the n-hexane extract were Staphylococcus epidermidis ATCC 12228 and Candida albicans YP0175, for which a MIC value of 13.0 μg/mL was scored.